Evaluación de la calidad seminal de dos razas ovina (Ovis orientalis aries), con la adición de minerales, en la ganadería de la Facultad de Ciencias Agropecuaria de la Universidad Técnica de Babahoyo - Cobo Silva, Marley Ilaria (2024)
The objective of the research project was to evaluate the seminal quality of two sheep breeds (Dorper and Pelibuey), with the addition of minerals, in the livestock of the Faculty of Agricultural Sciences of the Technical University of Babahoyo. In reference to the methodology, the research design, a quantitative approach is adopted. Regarding the results, each seminal sample was obtained using standardized semen collection, preservation and analysis techniques. The choice of three samples per race sought to provide an adequate representation of the interracial variability in terms of seminal quality. The extraction was carried out. of semen from male sheep using manual stimulation techniques and then extracting it with the electroejaculator, guaranteeing careful and respectful handling to minimize stress on the animals. Subsequently, seminal quality was evaluated using laboratory techniques such as the Neubauer chamber, using vital stains such as eosin-nigrosin, observed under the microscope and a pH electrode was used. In conclusion, the evaluation carried out on the semen quality of the two Dorper and Pelibuey sheep breeds during the mineral addition process has considered the parameters based on the mobility, concentration and morphology of the sperm. It has been shown that the Dorper breed has better seminal parameter than the Pelibuey breed by which the importance of reproductive efficiency is determined.